Nitrogen-fixing cereals a step nearer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Every farmer's dream of growing cereals that fix atmospheric nitrogen in the same way as leguminous plants has come a step nearer. Scientists at Nottingham University, UK, have successfully persuaded rice plants to grow nodules. For decades...